Relationship between population growth and economic development in developing East African countries - Mwai, Jane Wangari (Strathmore University, 2021)
The relationship between population growth and economic development has been a complex issue for decades and is yet to find a clear-cut solution. Some researchers have found a negative relationship, others a positive relationship while others found no relation at all in both developing and high-income countries. This study uses historical data to draw conclusions as to whether there exists a relationship, and what type of relation exist if any, between population growth and economic growth for the East African Community countries in the period 1986 to 2018. The findings of this study indicate mixed results with the existence of long run cointegration, positive causal unidirectional relationship in the countries. However, from the findings there seems to be no long run relationship for majority of the East African Community countries. This means that population growth has positive impacts on per capita GDP growth and thus economic growth for some of the countries and not in others.
Submitted in partial fulfillment of the requirements for the Degree of [Bachelor of Business Science in Actuarial Science] at Strathmore University